Reproduction of "Teaching Norms: Direct Evidence of Parental Transmission" - Martín Brun; Micole De Vera; Valon Kadriu; Fabian Mierisch (Institute for Replication (I4R), 2024)
This paper is a replication study of Brouwer, T., Galeotti, F., & Villeval, M. C. (2023), using the original data. The study explores how social norms are transmitted from one generation to another, specifically from parents to children. The authors conducted a field experiment involving 601 parents of children aged 3 to 12 in Lyon, France, to examine whether parents engage more in norm enforcement in the presence of their child, and whether the nature of punishment changes in the presence of the child. The study found that parents do engage more in norm enforcement in the presence of their child, and tend to use more indirect punishment when their child is present. This study highlights the role that parents play in transmitting social norms to their children. The replication analysis was successful, with the results of the original study being robust to changes in the model specification.
Keywords: 330; replication; experiment; information provision; inequality; field experiment